Removal of Metronidazole Antibiotic from Hospital Wastewater by Biosorbent Prepared from Plantain Wood - AI Amouei; D Naghipour; K Taghavi; M Estaji (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2020)
BACKGROUND AND OBJECTIVE: The overuse of antibiotics in hospitals and the entry of these pollutants into water resources is one of the major challenges to the health of the community and the environment. Removal of antibiotics from hospital wastewater and other aquatic environments is possible through the adsorption process. This study was performed to evaluate antibiotic removal using plantain wood due to being cheapn and natural. METHODS: In this in vitro study, the effect of pH (2, 4, 6, 8, 10 and 12), contact time (5, 10, 20, 40, 60, 80, 100 and 120 minutes), initial metronidazole concentration (10, 50 and 100 mg/L) and biosorbent dose (0.2, 0.4, 0.6, 0.8, 1, 1.2 and 1.4 g) on metronidazole removal rate in synthetic solution were evaluated, and the isothermal kinetic and thermodynamic results of the adsorption process were investigated in this study. Concentration of metronidazole in aqueous solution was measured by Hach DR 5000 UV-Vis Laboratory Spectrophotometer. FINDINGS: Maximum removal of metronidazole (91%) was obtained at pH=6.5, 60 min, initial concentration of 50 mg/l, adsorbent dose of 0.8 g and 25 °C and maximum adsorption capacity (11.38 mg/g) was obtained at a dosage of 0.1 g. In this study, the reaction rate followed the pseudo-second order and adsorption isotherm followed Langmuir equation. The adsorption thermodynamic results showed that the adsorption process is physical in nature and is a spontaneous endothermic reaction. CONCLUSION: The results of the study showed that biosorbent prepared from plantain wood is a natural material and has the ability to remove metronidazole antibiotics from hospital wastewater and other aquatic environments.